Atomic layer deposition and properties of ZrO2/Fe2O3 thin films - Kalam, Kristjan; Seemen, Helina; Ritslaid, Peeter; Rähn, Mihkel; Tamm, Aile; Kukli, Kaupo; Kasikov, Aarne; Link, Joosep; Stern, Raivo; Dueñas, Salvador; Castán, Helena; García, Héctor (Beilstein Journal of Nanotechnology, 2018)
Thin solid films consisting of ZrO2 and Fe2O3 were grown by atomic layer deposition (ALD) at 400 °C. Metastable phases of ZrO2 were stabilized by Fe2O3 doping. The number of alternating ZrO2 and Fe2O3 deposition cycles were varied in order to achieve films with different cation ratios. The influence of annealing on the composition and structure of the thin films was investigated. Additionally, the influence of composition and structure on electrical and magnetic properties was studied. Several samples exhibited a measurable saturation magnetization and most of the samples exhibited a charge polarization. Both phenomena were observed in the sample with a Zr/Fe atomic ratio of 2.0.
Keywords: atomic layer deposition; metal oxides; thin films